Growth Spectrum Complexity Dictates Aromatic Intensity in Coriander (Coriandrum sativum L.) - McAusland, Lorna; Lim, Mui-Ting; Morris, David E.; Smith-Herman, Hayley L.; Mohammed, Umar; Hayes-Gill, Barrie R.; Crowe, John A.; Fisk, Ian D.; Murchie, Erik H. (Frontiers in Plant Science, 2020)
Advancements in availability and specificity of light-emitting diodes (LEDs) have facilitated trait modification of high-value edible herbs and vegetables through the fine manipulation of spectra. Coriander (Coriandrum sativum L.) is a culinary herb, known for its fresh, citrusy aroma and high economic value. Studies into the impact of light intensity and spectrum on C. sativum physiology, morphology and aroma are limited. Using a Nasal Impact Frequency (NIF) panel, a selection of key compounds associated with the characteristic aroma of coriander were identified. Significant differences (P < 0.05) were observed in the concentration of these aromatics between plants grown in a controlled environment chamber under the same photosynthetic photon flux density but custom spectra: red (100%), blue (100%), red+blue (RB, 50% equal contribution) or red+green+blue (RGB, 35.8% red: 26.4% green: 37.8% blue) wavelengths. In general, the concentration of aromatics increased with increasing numbers of wavelengths emitted alongside selective changes e.g. the greatest increase in coriander-defining E-(2)-decenal occurred under the RGB spectrum. This change in aroma profile was accompanied by significant differences (P < 0.05) in light saturated photosynthetic CO2 assimilation, water-use efficiency and morphology. While plants grown under red wavelengths achieved the greatest leaf area, RB spectrum plants were shortest and had the highest leaf:shoot ratio. Therefore, this work evidences a trade-off between sellable commercial morphologies with a weaker, less desirable aroma or a less desirable morphology with more intense coriander-like aromas. When supplemental trichromatic LEDs were used in a commercial glasshouse, the majority of compounds, with the exception of linalool, also increased showing that even as a supplement additional wavelengths can modify the aromatic profile increasing its complexity. Lower levels of linalool suggest these plants may be more susceptible to biotic stress such as herbivory. Finally, the concentration of coriander-defining aromatics E-(2)-decenal and E-(2)-hexenal were significantly higher in supermarket pre-packaged coriander leaves implying that concentrations of aromatics increase after excision. In summary, spectra can be used to co-manipulate aroma profile and plant form with increasing spectral complexity leading to greater aromatic complexity and intensity. We suggest that increasing spectral complexity progressively stimulates signalling pathways giving rise to valuable economic traits.